Development and the Interaction of Enforcement Institutions - Dhillon, Amrita (2012)
We examine how formal and informal contract enforcing institutions interact in a competitive market with asymmetric information where consumers do not observe quality before purchase. Firm level incentives for producing high quality can be achieved with an informal enforcement mechanism, reputation, the efficacy of which is enhanced by consumers investing in "connectedness;" or with a formal mechanism, legal enforcement, the effectiveness of which can be reduced by means of bribes. We show that formal and informal enforcement mechanisms do not necessarily substitute each other: while high levels of judicial efficiency decrease consumers' incentives to connect, higher consumers' connectedness leads to higher levels of judicial efficiency. We then look at how the equilibrium institutional mix evolves with the level of development. In doing so we show the presence of a new, physical, channel that can affect institutions--i.e., the frequency of bad productivity shocks that, in less developed settings, can impact on firms' incentives to cheat.